In Vitro Antibacterial Activity of Adhesive Systems on Streptococcus Mutans - Paradella, Thais Cachute [UNESP]; Koga-Ito, Cristiane Yumi [UNESP]; Cardoso Jorge, Antonio Olavo [UNESP] (Quintessence Publishing Co Inc, 2009)
Purpose: To evaluate the antibacterial activity of three adhesive systems - Prime & Bond 2.1 (PB), Clearfil SE Bond (CS) and One Up Bond F (OU) - on Streptococcus mutans in vitro.Materials and Methods: Adherence and agar disk-diffusion tests were performed. For the adherence testing, 40 human enamel specimens (4 mm(2)) were sterilized and the adhesive sytems were applied (n = 10). The control group did not receive the application of any adhesive system. Specimens were immersed in brain heart infusion broth (BHI) inoculated with S. mutans standardized suspension (106 cells/ml) for 48 h at 37 degrees C and 5% CO(2). The number of S. mutans cells adhered to each specimen was evaluated by the plating method on BHI agar. For agar disk-diffusion testing, adhesive disks and disks soaked in distilled water (negative control) or 0.2% chlorexidine (positive control) were incubated with S. mutans for 48 h. The diameters of the zones of bacterial inhibition were measured. Adherence data were transformed in logarithms of base 10 (log(10)). Data were submitted to Kruskal-Wallis and Student-Neuman-Keuls tests at the 5% level of significance.Results: The results of the adherence test showed that One Up Bond F (OU) and Clearfil SE Bond (CS) did not differ significantly from one another, but allowed significantly less adherence than Prime & Bond 2.1 (PB) and control [mean log(10) (standard deviation) values: PB 6.10 (0.19); CS primer 4.55 (0.98); OU 4.65 (0.54); control group 6.34 (0.27)]. The disk-diffusion test showed no significant difference between OU (diameter in mm: 3.02 +/- 0.13) and CS (3.0 +/- 0.12), but both were significantly more effective in inhibiting bacteria] growth than PB (1.0 +/- 0.10).Conclusion: The self-etching systems Clearfil SE Bond and One Up Bond F presented a greater inhibitory effect against S. mutans, also in terms of adherence, than did the conventional system, Prime & Bond 2.1.
Keywords: Streptococcus mutans; adhesive systems; enamel